2012
DOI: 10.1002/ejic.201200883
|View full text |Cite
|
Sign up to set email alerts
|

Interactions between Keggin Anions in Water: The Higher Their Charge, the Higher Their Condensation? A Simulation Study

Abstract: We report molecular dynamics (MD) 5-), the aim of which was to investigate whether the anions increasingly repulse each other in water when their charge increases from -3 to -5. The MD and PMF (potential of mean force) results indicate that this is not the case. All three anions are found to display short XW n-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
42
1
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(53 citation statements)
references
References 88 publications
8
42
1
2
Order By: Relevance
“…Information on dynamic processes of POM-cation interactions can be accessed by classical and ab initio molecular dynamics (MD) simulations. [55][56][57][58] For example, MD was used in conjunction with the above-mentioned microscopy study, and both independently showed formation of POM-pairs linked by Na + , also consistent with the solid-state structure. [51] In summary, the combination of experiment and theory can potentially provide powerful and accurate information about POM-cation interactions in solution, guiding future developments of new POM architectures and superstructures.…”
Section: Experimental and Theoretical Methods To Explore Cation-pom Amentioning
confidence: 56%
See 1 more Smart Citation
“…Information on dynamic processes of POM-cation interactions can be accessed by classical and ab initio molecular dynamics (MD) simulations. [55][56][57][58] For example, MD was used in conjunction with the above-mentioned microscopy study, and both independently showed formation of POM-pairs linked by Na + , also consistent with the solid-state structure. [51] In summary, the combination of experiment and theory can potentially provide powerful and accurate information about POM-cation interactions in solution, guiding future developments of new POM architectures and superstructures.…”
Section: Experimental and Theoretical Methods To Explore Cation-pom Amentioning
confidence: 56%
“…Thereby, experimentally accessible data such as vibrational or electronic absorption properties can be calculated from first principles, and characteristic features of the POM–cation interactions can be identified. Information on dynamic processes of POM–cation interactions can be accessed by classical and ab initio molecular dynamics (MD) simulations . For example, MD was used in conjunction with the above‐mentioned microscopy study, and both independently showed formation of POM‐pairs linked by Na + , also consistent with the solid‐state structure .…”
Section: Introduction: Fundamentals Of Pom–cation Interactionsmentioning
confidence: 99%
“…Is has been shown among others by Liu 21 and Weinstock 22 that self-assembly of POM clusters is affected by the counterions. Molecular dynamic simulations of Keggin clusters in acid aqueous environment performed by Chaumont and Wipff 23 also show that SiW 12 O 40 4– exhibits a larger tendency of aggregation compared to PW 12 O 40 3– , despite its higher charge. Furthermore, they found that the distance between the aggregated clusters changes only marginally (0.1 Å).…”
Section: Discussionmentioning
confidence: 89%
“…Dadurch können experimentell beobachtbare Daten wie Schwingungs‐ und elektronische Absorptionsspektren basierend auf Ab‐initio‐Methoden berechnet und charakteristische Eigenschaften der POM‐Kation‐Wechselwirkungen identifiziert werden. Informationen über dynamische Prozesse der POM‐Kation‐Wechselwirkungen können zudem durch klassische und Ab‐initio‐Moleküldynamik(MD)‐Simulationen zugänglich gemacht werden . So wurde z.…”
Section: Einleitung: Grundlagen Der Pom‐kation‐wechselwirkungenunclassified
“…Informationen über dynamische Prozesse der POM-Kation-Wechselwirkungen kçnnen zudem durch klassische und Ab-initio-Moleküldynamik(MD)-Simulationen zugänglich gemacht werden. [55][56][57][58] So wurde z. B. MD zusammen mit der oben beschriebenen Mikroskopiestudie genutzt, um unabhängig voneinander die Bildung von Na + -verknüpften POM-Paaren nachzuweisen, was auch konsistent mit der beobachteten Festkçrperstruktur war.…”
Section: Lçslichkeit Und Ionenpaarbildungunclassified